ACKNOWLEDGEMENTS. (20th March 2014) - Unknown
Abstract : This edition has been many years in the making and has left me with numerous debts. I first began working with Anne Bacon's letters during my doctoral research. After my initial despair over the indecipherable nature of Anne's handwriting, the correspondence formed an important part of my thesis and subsequent monograph. I owe a huge debt of gratitude to Felicity Heal, who supervised my doctoral studies and who has been kind enough to guide and encourage my labours ever since. The suggestion that I should compile an edition first came from James Daybell, over a cup of tea in Blackwell's coffee shop in Oxford. I am very much indebted to James for his support of the project ever since and for generously sharing his expertise in early modern epistolary culture. Lynne Magnusson and Alan Stewart both read the edition in its entirety at a particularly busy point in the academic year. I am hugely grateful for their herculean efforts; their erudition and detailed knowledge of the Bacon archive has saved me from countless errors. As literary director for the Camden series, Ian Archer has shown unstinting patience as more letters were discovered and deadlines were revised; I am grateful too for his perceptive comments on various letters. Many other scholars were generous with advice and references, including Timothy Barnes, Susan Brigden, Susan Doran, Clive Holmes, Diarmaid MacCulloch, Michael McVaugh, Alison Wall, and Alison Wiggins. My colleagues at both Pembroke College and, more recently, the Open University have encouraged my labours with the letters; I am most grateful to them all and in particular to Eleanor Betts, Amanda Goodrich, Helen King, Anne Laurence, Donna Loftus, Rosemary O'Day, and Gabriella Zuccolin. I must also acknowledge the patience shown by my students, for indulging my enthusiasm when Anne Bacon letters made appearances in tutorials.